The Evolution of Bitcoin: A Historical Analysis and Future Prospects - Hossaion, Shohal; Bairagi, Mithun; Aktar, Jasmin; Honey, Umme; Mithy, Samme Akter (iRASD Journal of Economics, 2023)
Bitcoin is the first decentralized digital currency that was introduced in 2009 and has since garnered significant attention from investors, governments, and the general public. This research article provides a comprehensive historical analysis of the evolution of Bitcoin, tracing its roots from its early days as a niche, experimental technology to its current status as a global financial phenomenon. The study explores the key events and milestones in Bitcoin's development, including the creation of the first block chain, the emergence of cryptocurrency exchanges, and the proliferation of Bitcoin mining. It also delves into the economic and social factors that have influenced Bitcoin's growth and adoption over time, including government regulation, market fluctuations, and the rise of alternative cryptocurrencies. Furthermore, the article examines the potential future prospects of Bitcoin, including its potential to disrupt traditional financial systems, its viability as a long-term investment asset, and the emerging trends in the broader cryptocurrency ecosystem. The study concludes by highlighting the significance of Bitcoin as a transformative technology with significant implications for the global financial system. The insights provided by this research can aid policymakers, investors, and researchers in understanding the past, present, and future prospects of Bitcoin and its role in shaping the future of finance.